Calculation of Actuarial Values Using The Result of The 2019 Makeham Mortality Law Contruction and The Cox Ingersoll Ros - M, Suriani; Nursamsi, Nursamsi; Hukmah, Hukmah; Sulma, Sulma; Nisardi, Muhammad Rifki (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2023)
Premium is an amount of money that must be paid by the customer at a certain time based on the insurance policy. This study aims to determine the value of whole life insurance premiums using the Makeham mortality law method and the Cox Ingersoll Ross (CIR) model. The result of the study obtained the calculation of interest rates using the CIR model, the smaller the value, the greater discount and the premium paid using the Makeham mortality law method was Rp. 102.478 < premium < Rp. 1.270.630 / Mounth.